Branchpoints as potential targets of exon-skipping therapies for genetic disorders - Hiroaki Ohara; Motoyasu Hosokawa; Tomonari Awaya; Atsuko Hagiwara; Ryo Kurosawa; Yukiya Sako; Megumu Ogawa; Masashi Ogasawara; Satoru Noguchi; Yuichi Goto; Ryosuke Takahashi; Ichizo Nishino; et al. (Elsevier, 2023)
Fukutin (FKTN) c.647+2084G>T creates a pseudo-exon with a premature stop codon, which causes Fukuyama congenital muscular dystrophy (FCMD). We aimed to ameliorate aberrant splicing of FKTN caused by this variant. We screened compounds focusing on splicing regulation using the c.647+2084G>T splicing reporter and discovered that the branchpoint, which is essential for splicing reactions, could be a potential therapeutic target. To confirm the effectiveness of branchpoints as targets for exon skipping, we designed branchpoint-targeted antisense oligonucleotides (BP-AONs). This restored normal FKTN mRNA and protein production in FCMD patient myotubes. We identified a functional BP by detecting splicing intermediates and creating BP mutations in the FKTN reporter gene; this BP was non-redundant and sufficiently blocked by BP-AONs. Next, a BP-AON was designed for a different FCMD-causing variant, which induces pathogenic exon trapping by a common SINE-VNTR-Alu-type retrotransposon. Notably, this BP-AON also restored normal FKTN mRNA and protein production in FCMD patient myotubes. Our findings suggest that BPs could be potential targets in exon-skipping therapeutic strategies for genetic disorders.